A universal method for preparing polymer nanoparticles

By using ZIF-8 as a template and performing chemical crosslinking reactions, the problem of complex and uncommon preparation methods of polymer nanoparticles in the prior art is solved, and the simple and rapid preparation and property regulation of polymer nanoparticles are achieved, which is suitable for multiple A polymer material.

CN115403791BActive Publication Date: 2025-02-25SHANDONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211115829.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-14
Publication Date
2025-02-25
Estimated Expiration
2042-09-14

AI Technical Summary

Technical Problem

The prior art has problems such as complex methods and no universality in preparing polymer nanoparticles, which are difficult to effectively regulate the physical and chemical properties of nanoparticles, and the template removal process is complicated.

Method used

ZIF-8 is used as a self-sacrifice template, and the polymer precursor and crosslinking agent are crosslinked in acid buffer solution through different chemical crosslinking reactions to realize the preparation of polymer nanoparticles and degradation of ZIF-8. Remove the template.

Benefits of technology

The universal preparation method of polymer nanoparticles is realized, which can easily and quickly regulate the size and hardness of nanoparticles, and impart different responsive degradation abilities. It is suitable for various polymers such as polysaccharides, peptides, and proteins.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115403791B_ABST
    Figure CN115403791B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing polymer nanoparticles such as synthetic polymers, polypeptides, polysaccharides, proteins, etc. using ZIF-8 as a template. The prepared polymer nanoparticles can complete the cross-linking of polymers through thiol-disulfide bond exchange reaction, Schiff base reaction, amidation reaction and click reaction, etc., and are suitable for the synthesis of various polymer nanoparticles, and have universality. By changing the reaction concentration of polymer precursor and cross-linking agent, the size and hardness of polymer nanoparticles can be respectively regulated, and the regulation of the physical and chemical properties of polymer nanoparticles can be taken into account. The prepared nanoparticles have potential application value in drug and vaccine delivery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer nanoparticle preparation, and in particular to a universal method for preparing polymer nanoparticles. Background Art

[0002] Polymer nanoparticles are mainly prepared from synthetic polymers and natural polymers through various synthetic methods. They have adjustable size, morphology, surface chemistry, physical and chemical properties such as softness and hardness, and good biocompatibility. They have certain application value in enzyme catalysis, drug delivery, targeted imaging, and energy conversion.

[0003] Template method is the most commonly used method for preparing polymer nanoparticles, among which layer-by-layer self-assembly technology is widely used. This method is to coat various target polymers on the template to form a functional coating by immersion, spraying or spin coating, using electrostatic force, host-guest interaction, specific biological reaction, hydrogen bond, covalent bond and other interactions. Various polymer nanoparticles prepared by this method have been widely used in biochemistry, drug sustained release and other aspects. However, the layer-by-layer self-assembly technology has the disadvantages of complex preparation process, time-consuming and labor-intensive.

[0004] The preparation of polymer nanoparticles using mesoporous silica templates can avoid the disadvantage of many coating layers in layer-by-layer self-assembly technology, and the preparation of polymer nanoparticles using mesoporous silica as a template can well regulate the physical and chemical properties of nanoparticles. However, this method has certain requirements on the types of polymers involved in the reaction, and the removal of the mesoporous silica template requires harsh conditions such as hydrofluoric acid, which have an adverse effect on the synthesis and application of polymer nanoparticles. Therefore, the development of a new universal method for preparing polymer nanoparticles, which can not only achieve the on-demand regulation of various physical and chemical properties of nanoparticles, but also achieve the simple removal of the template, has important theoretical and practical significance.

[0005] Zeolite imidazolate framework material (ZIF-8) is a metal organic framework material formed by the coordination of zinc ions and dimethylimidazole. When polyethylene glycol (PEG) is used as a mineralizer, it can encapsulate various synthetic polymers and biological macromolecules such as proteins, and it will degrade under acidic conditions to achieve controlled release of encapsulated substances; at the same time, the size of ZIF-8 nanoparticles can be controlled by controlling the reaction temperature. Therefore, ZIF-8 is an ideal template for encapsulating polymers. Summary of the invention

[0006] In view of the shortcomings of existing methods for preparing polymer nanoparticles, such as being complex and not universal, the present invention provides a universal method for preparing polymer nanoparticles.

[0007] The first aspect of the present invention provides a universal method for preparing polymer nanoparticles through different chemical cross-linking reactions and the polymer nanoparticles obtained by the above method. The steps include:

[0008] The mineralizer and the polymer precursor are dissolved in a 2-methylimidazole aqueous solution, and then the solution is mixed with a zinc nitrate aqueous solution. After the reaction, the supernatant is removed by centrifugation, and then the product is redispersed in water and washed by centrifugation three times to obtain ZIF-8 nanoparticles encapsulating the polymer precursor. Subsequently, the ZIF-8 nanoparticles are dispersed in an acidic buffer solution containing a polymer crosslinking agent, the reaction solution is poured into a dialysis bag, and then placed in an acidic buffer solution for degradation of ZIF-8 and crosslinking reaction between the polymer precursor and the polymer crosslinking agent. After the reaction is completed, the reaction solution in the dialysis bag is taken out and centrifuged, and the product is washed three times with water to obtain polymer nanoparticles.

[0009] The second aspect of the present invention takes polysaccharides, polypeptides and proteins as examples to provide a universal method for preparing nanoparticles applicable to various polymers and the nanoparticles prepared by the method. The steps are as follows:

[0010] The mineralizer and the polymer precursor are dissolved together in a 2-methylimidazole aqueous solution, and then the above solution is mixed with a zinc nitrate aqueous solution. After the reaction, the supernatant is removed by centrifugation, and then the product is redispersed in water and washed by centrifugation three times to obtain ZIF-8 nanoparticles encapsulating the polymer precursor. Subsequently, the ZIF-8 nanoparticles are dispersed in an acidic buffer solution containing a polymer crosslinking agent, the reaction solution is poured into a dialysis bag, and then placed in an acidic buffer solution for degradation of ZIF-8 and crosslinking reaction between the polymer precursor and the polymer crosslinking agent. After the reaction is completed, the reaction solution in the dialysis bag is taken out and centrifuged, and the product is washed three times with water to obtain polymer nanoparticles.

[0011] The third aspect of the present invention provides an application of the polymer nanoparticles prepared by the above method in biomedicine (such as enzyme catalysis, drug and vaccine delivery, etc.).

[0012] One or more embodiments of the present invention have at least the following beneficial effects:

[0013] This method is applicable to the preparation of polymer nanoparticles from various polymers such as polysaccharides, peptides, proteins and synthetic polymers, which means that this method is universal.

[0014] The invention uses ZIF-8 as a self-sacrificial template to prepare polymer nanoparticles from the outside to the inside, and realizes crosslinking between the polymer precursor and the polymer crosslinking agent while ZIF-8 is degraded, and no additional step is required to remove the template. The preparation method is simple, rapid, highly operable, and can be prepared in large quantities.

[0015] In the present invention, the size of ZIF-8 nanoparticles can be adjusted by regulating the reaction concentration of the polymer precursor, thereby controlling the size of the polymer nanoparticles synthesized using ZIF-8 as a template; in addition, the hardness of the polymer nanoparticles can also be regulated by regulating the reaction concentration of the polymer crosslinking agent.

[0016] The synthesis of the polymer nanoparticles in the present invention is completed by four different cross-linking reactions (thiol-disulfide bond exchange reaction, Schiff base reaction, amidation reaction and click chemistry reaction), forming different chemical bonds, thereby giving the polymer nanoparticles different responsive degradation capabilities, providing conditions for various applications of the polymer nanoparticles. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 a is a schematic diagram of the process of preparing polymer nanoparticles using ZIF-8 nanoparticles as templates; Figure 1 b shows the four cross-linking reactions involved in the synthesis of polymer nanoparticles.

[0018] Figure 2 ac are schematic diagrams of the structures of 8-arm-PEG-MAL, 8-arm-PEG-NDEC and 8-arm-PEG-NH2, respectively; Figure 2 df are TEM images of 8-arm-PEG-MAL@ZIF-8, 8-arm-PEG-NDEC@ZIF-8 and 8-arm-PEG-NH2@ZIF-8, respectively; Figure 2 gi is corresponding Figure 2 df shows PEG nanoparticles prepared using ZIF-8 as a template. The scale bar in the figure is 1 μm.

[0019] Figure 3 ad are schematic diagrams of the structures of HA-SH, PLL-SH, OVA-SH and LYZ, respectively; Figure 3 eh are the TEM images of HA-SH@ZIF-8, PLL-SH@ZIF-8, OVA-SH@ZIF-8 and LYZ@ZIF-8, respectively; Figure 3 il is the corresponding Figure 3 HA nanoparticles, PLL nanoparticles, OVA nanoparticles, and LYZ nanoparticles prepared using ZIF-8 in eh as a template. The scale bar in the figure is 1 μm.

[0020] Figure 4 ad are the HA-SH@ZIF-8 nanoparticles prepared when the mass of HA-SH is 1 mg, 4 mg, 10 mg and 16 mg respectively; Figure 4 eh is the corresponding Figure 4HA-SH@ZIF-8 nanoparticles in ad are HA nanoparticles prepared using 8-arm-PEG-TNB as a crosslinker. The scale bar in the figure is 500 nm.

[0021] Figure 5 Statistical data of Young's modulus of HA nanoparticles prepared with different cross-linking agent concentrations.

[0022] Figure 6 The stability data of HA nanoparticles prepared by thiol-disulfide exchange reaction and PEG nanoparticles prepared by Schiff base reaction in different media.

[0023] Figure 7 a is a schematic diagram of the polymer particle formation process; Figure 7 b. Figure 7 c. Figure 7 d. Figure 7 e are confocal fluorescence imaging images of HA particles at 10 minutes, 20 minutes, 30 minutes and 60 minutes in the formation process. The scale bar in the figure is 2 μm.

[0024] Figure 8 This is the release curve of OVA from OVA nanoparticles in GSH (10 mM) solution.

[0025] Fig. 9 Results of the cell interaction experiment after free OVA and OVA nanoparticles at different concentrations were co-incubated with RAW 264.7 cells for 6 hours.

[0026] Fig.10 Statistical data for BMDC cell maturation experiment.

[0027] Fig.11 Statistical data for antigen presentation experiments in BMDC cells. DETAILED DESCRIPTION

[0028] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0029] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0030] As described in the background art, the existing methods for preparing polymer nanoparticles are still complicated and not universal. Therefore, developing a universal method for preparing polymer nanoparticles is of great significance for the application of polymer nanoparticles in various fields.

[0031] In order to solve the above technical problems, the first aspect of the present invention provides a universal method for preparing polymer nanoparticles by different chemical cross-linking reactions: dissolving a mineralizer and a polymer precursor in a 2-methylimidazole aqueous solution, then blending the above solution with a zinc nitrate aqueous solution for reaction, centrifuging to remove the supernatant after the reaction, then redispersing the product in water and centrifuging and washing the product to obtain ZIF-8 nanoparticles encapsulating the polymer. Subsequently, the ZIF-8 nanoparticles are dispersed in an acidic buffer solution containing a polymer cross-linking agent, the reaction solution is poured into a dialysis bag, and then placed in an acidic buffer solution for degradation of ZIF-8 and cross-linking reaction between the polymer precursor and the polymer cross-linking agent, and after the reaction is completed, the reaction solution in the dialysis bag is taken out and centrifuged, and the product is washed three times with water to obtain polymer nanoparticles.

[0032] The mineralizer is PEG.

[0033] The polymer precursors are various polymers.

[0034] Furthermore, when the prepared polymer nanoparticles are PEG nanoparticles, PEG is both a mineralizer and a polymer precursor.

[0035] Further, PEG is 8-arm-PEG-Maleimide (8-arm-PEG-MAL), 8-arm-PEG-4-nitrophenyl-2-(2-pyridyldithio)ethyl carbonate (8-arm-PEG-NDEC) or 8-arm-PEG-NH2, and its molecular weight is 10 kDa, 20 kDa or 40 kDa. Further preferably, the molecular weight of 8-arm-PEG-MAL is 20 kDa, the molecular weight of 8-arm-PEG-NDEC is 40 kDa, and the molecular weight of 8-arm-PEG-NH2 is 20 kDa.

[0036] The synthetic route of 8-arm-PEG-NDEC is shown in Scheme 1:

[0037]

[0038] Route 1

[0039] The concentration of PEG in the 2-methylimidazole aqueous solution is 2.5-100 mg mL -1 .

[0040] In the 2-methylimidazole aqueous solution, the concentration of 2-methylimidazole is 120-200 mM.

[0041] In the zinc nitrate aqueous solution, the concentration of zinc nitrate is 30-70 mM.

[0042] The volume ratio of the 2-methylimidazole aqueous solution to the zinc nitrate aqueous solution is (1-2): (1-2). More preferably, the volume ratio of the 2-methylimidazole aqueous solution to the zinc nitrate aqueous solution is 1:1.

[0043] The reaction time for preparing ZIF-8 nanoparticles encapsulating polymers is 20-40 minutes.

[0044] The time for the degradation of ZIF-8 and the cross-linking reaction of PEG molecules is 1-8 hours.

[0045] The ZIF-8 nanoparticles were centrifuged at a speed of 1000-10000 rcf.

[0046] Corresponding to 8-arm-PEG-MAL, 8-arm-PEG-NDEC or 8-arm-PEG-NH2 encapsulated in ZIF-8, the PEG cross-linking agent is 8-arm-PEG-SH, 8-arm-PEG-NH2 or 8-arm-PEG-CHO, with molecular weights of 10 kDa, 20 kDa and 40 kDa. The cross-linking reactions are click chemistry reaction, amidation reaction and Schiff base reaction.

[0047] Furthermore, the molecular weight of 8-arm-PEG-SH is 20 kDa, the molecular weight of 8-arm-PEG-NH2 is 10 kDa, and the molecular weight of 8-arm-PEG-CHO is 10 kDa; the concentration of PEG crosslinker in the acidic buffer solution is 0.2-15 mg mL -1 .

[0048] The acidic buffer solution is a sodium acetate buffer solution with a concentration of 50 mM and a pH of 5.5-6.0.

[0049] When dialysis is performed in an acidic buffer solution, the molecular weight cutoff of the dialysis bag used is 1-7 kDa, and more preferably, the molecular weight cutoff of the dialysis bag is 3.5 kDa.

[0050] The second aspect of the present invention provides a universal method for preparing nanoparticles of various polymers, taking polysaccharides, polypeptides and proteins as examples. The method comprises the following steps:

[0051] The mineralizer and the polymer precursor are dissolved together in a 2-methylimidazole aqueous solution, and then the solution is mixed with a zinc nitrate aqueous solution, and the supernatant is removed by centrifugation after the reaction for 30 minutes, and then the product is redispersed in water and washed by centrifugation to obtain ZIF-8 nanoparticles encapsulating the polymer precursor. Subsequently, the ZIF-8 nanoparticles are dispersed in an acidic buffer solution containing a polymer crosslinking agent, the reaction solution is poured into a dialysis bag, and then placed in an acidic buffer solution for degradation of ZIF-8 and crosslinking reaction between the polymer precursor and the polymer crosslinking agent, and the reaction solution in the dialysis bag is taken out and centrifuged after 1-8 hours, and the product is washed three times with water to obtain polymer nanoparticles.

[0052] The mineralizer is 8-arm-PEG-OH, and the concentration of 8-arm-PEG-OH in the 2-methylimidazole aqueous solution is 2.5-100 mg mL -1 , further preferably, the concentration of 8-arm-PEG-OH in the 2-methylimidazole aqueous solution is 5 mg mL -1 .

[0053] The polymer precursor includes thiolated hyaluronic acid (HA-SH), thiolated polylysine (PLL-SH), thiolated ovalbumin (OVA-SH) or lysozyme (LYZ) and the like.

[0054] The polymer crosslinker is 8-arm-PEG-2-nitro-5-thiobenzoate (8-arm-PEG-TNB), and the concentration of 8-arm-PEG-TNB in ​​the acidic buffer solution is 0.2-15 mg mL -1 The cross-linking reaction that occurs is a thiol-disulfide bond exchange reaction.

[0055] The polymer nanoparticles are HA nanoparticles, PLL nanoparticles, OVA nanoparticles and LYZ nanoparticles respectively.

[0056] The above preparation method can effectively regulate the physical and chemical properties of the polymer, and the specific physical and chemical properties that can be regulated include: size, hardness and responsive degradation.

[0057] The third aspect of the present invention provides an application of the polymer nanoparticles prepared by the above method. The specific application is: 8-arm-PEG-NDEC is used as a cross-linking agent of OVA to prepare OVA nanoparticles, and then the application of OVA nanoparticles in immune antigen delivery is studied.

[0058] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0059] Example 1

[0060] Taking the synthesis of PEG nanoparticles as an example, a universal method for preparing polymer nanoparticles through different chemical cross-linking reactions is as follows:

[0061] 8-arm-PEG-MAL (20 kDa, 20 mg), 8-arm-PEG-NDEC (40 kDa, 20 mg), or 8-arm-PEG-NH2 (20 kDa, 20 mg) was dissolved in 2-methylimidazole aqueous solution, and the concentration of 2-methylimidazole was 160 mM;

[0062] Then it was added into the aqueous zinc nitrate solution, the concentration of the aqueous zinc nitrate solution was 40 mM;

[0063] After mixing and reacting for 30 minutes, the reaction solution was taken out, centrifuged and washed with water three times to obtain ZIF-8 nanoparticles encapsulating 8-arm-PEG-MAL, 8-arm-PEG-NDEC or 8-arm-PEG-NH2 (8-arm-PEG-MAL@ZIF-8, 8-arm-PEG-NDEC@ZIF-8 or 8-arm-PEG-NH2@ZIF-8), respectively. The relevant TEM characterization data are shown in Figure 2 df shown;

[0064] The product was dispersed in 300 μL of water and added to a sodium acetate buffer solution (50 mM, pH 5.5) containing a PEG crosslinker. The reaction solution was transferred to a dialysis bag with a molecular weight cutoff of 3.5 kDa. The dialysis bag was placed in a sodium acetate buffer solution for 4 hours and then taken out, centrifuged and washed with water three times to obtain the final product. The PEG crosslinkers corresponding to 8-arm-PEG-MAL@ZIF-8, 8-arm-PEG-NDEC@ZIF-8 or 8-arm-PEG-NH2@ZIF-8 were 8-arm-PEG-SH (20 kDa, 5 mg / mL), 8-arm-PEG-NH2 (20 kDa, 5 mg / mL) or 8-arm-PEG-CHO (20 kDa, 5 mg / mL). Four types of PEG nanoparticles were prepared by Schiff base reaction, amidation reaction and click chemistry reaction, respectively. TEM characterization is shown in Figure 2. Figure 2 As shown in gi.

[0065] Example 2

[0066] Taking polysaccharides, peptides and proteins as examples, it is proved that this method is a universal method for preparing nanoparticles of various polymers. The steps are as follows:

[0067] 8-arm-PEG-OH (40 kDa, 10 mg) was dissolved together with HA-SH, PLL-SH, OVA-SH, or LYZ in 2-methylimidazole aqueous solution (160 mM, 2 mL) and then poured into zinc nitrate aqueous solution (40 mM, 2 mL);

[0068] After half an hour of rotation and mixing, HA-SH@ZIF-8, PLL-SH@ZIF-8, OVA-SH@ZIF-8 or LYZ@ZIF-8 nanoparticles were formed (TEM images as shown in Figure 3 eh), which was centrifuged and washed with water and finally dispersed in 300 µL of water;

[0069] The above products were poured into a sodium acetate buffer solution (50 mM, pH 5.5) containing a cross-linking agent 8-arm-PEG-TNB (10 kDa, 5 mg / mL), and then transferred to a dialysis bag with a molecular weight cutoff of 3.5 kDa. The dialysis bag was placed in a sodium acetate buffer solution (50 mM, pH 5.5) for 4 hours and then taken out to obtain HA, PLL, OVA or LYZ nanoparticles (TEM images as shown in Figure 3 il), which was centrifuged and washed three times with water to obtain the final product.

[0070] Example 3

[0071] The size of polymer nanoparticles can be controlled by changing the reaction concentration of the polymer precursor. Taking the preparation of HA nanoparticles as an example, the steps are as follows:

[0072] 8-arm-PEG-OH (40 kDa, 10 mg) and different masses of HA-SH (1 mg, 4 mg, 10 mg, or 16 mg) were dissolved in 2-methylimidazole aqueous solution (160 mM, 2 mL) and then poured into zinc nitrate aqueous solution (40 mM, 2 mL);

[0073] After mixing and reacting for 30 min, the reaction solution was taken out, centrifuged and washed with water three times to obtain HA-SH@ZIF-8 of different sizes ( Figure 4 ad), and finally dispersed in 300 µL of water;

[0074] The above product was poured into a sodium acetate buffer solution (50 mM, pH 5.5) containing a cross-linking agent 8-arm-PEG-TNB (10 kDa, 5 mg / mL), and then transferred to a dialysis bag with a molecular weight cutoff of 3.5 kDa. The dialysis bag was placed in a sodium acetate buffer solution (50 mM, pH 5.5) for 4 hours and then taken out, centrifuged and washed with water three times to obtain the final product. The sizes of the four HA nanoparticles obtained were 200 nm, 500 nm, 750 nm and 1200 nm ( Figure 4 Therefore, the size of ZIF-8 nanoparticles can be regulated by changing the concentration of the polymer, and thus the size of the polymer nanoparticles can be regulated.

[0075] Example 4

[0076] The hardness of polymer nanoparticles can be regulated by changing the reaction concentration of the polymer crosslinking agent. Taking the preparation of HA nanoparticles as an example, the steps are as follows:

[0077] 8-arm-PEG-OH (40 kDa, 10 mg) and HA-SH (10 mg) were dissolved in 2-methylimidazole aqueous solution (160 mM, 2 mL) and then added to zinc nitrate aqueous solution (40 mM, 2 mL);

[0078] After mixing for 30 min, the reaction solution was taken out, centrifuged and washed three times with water, and finally dispersed in 300 μL of water;

[0079] The above products were added to sodium acetate buffer solution (50 mM, pH 5.5) containing different concentrations of cross-linking agent 8-arm-PEG-TNB (0.25 mg / mL, 1 mg / mL, 2.5 mg / mL or 4 mg / mL), and then transferred to a dialysis bag with a molecular weight cutoff of 3.5 kDa. The dialysis bag was placed in sodium acetate buffer solution (50 mM, pH 5.5) for 4 hours and then taken out, centrifuged and washed with water three times to obtain the final product. The four HA nanoparticles obtained were characterized by AFM, and their respective Young's moduli were measured. The statistical results are shown as follows: Figure 5 The experimental results show that changing the concentration of the cross-linking agent can effectively control the hardness of polymer nanoparticles.

[0080] Example 5

[0081] Different cross-linking strategies are used to make polymer nanoparticles have different responsive degradation properties. The steps are as follows:

[0082] pH-responsive PEG nanoparticles were prepared using 8-arm-PEG-NH2@ZIF-8 as a template and 8-arm-PEG-CHO as a cross-linker via a Schiff base reaction.

[0083] Using HA-SH@ZIF-8 as a template and 8-arm-PEG-TNB as a cross-linker, HA nanoparticles with reduction responsiveness were prepared through a thiol-disulfide bond exchange reaction.

[0084] After the above PEG nanoparticles and HA nanoparticles were fluorescently labeled, they were placed in PBS, sodium acetate buffer solution (pH 5.0) or reduced glutathione solution (GSH, 10 mM), respectively. 50 μL of the mixed solution was taken out at different set time points, and the number of nanoparticles in the mixed solution was detected using a flow cytometer. The experimental results are shown in Figure 2. Figure 6 As shown, the above-mentioned PEG nanoparticles and HA nanoparticles have very good stability in PBS. PEG nanoparticles are gradually degraded in acidic buffer solution, and HA nanoparticles are also gradually degraded under reducing conditions. This proves that by selecting different cross-linking strategies, different responsive degradability can be given to nanoparticles, thereby achieving responsive release of internal encapsulated substances.

[0085] Example 6

[0086] Taking the synthesis of HA nanoparticles as an example, the formation process of polymer nanoparticles was characterized by confocal microscopy. The steps are as follows:

[0087] 8-arm-PEG-OH (40 kDa, 10 mg) and thiopyridinyl HA (HA-PDA) (10 mg) were dissolved in 2-methylimidazole aqueous solution (160 mM, 2 mL), and then added to zinc nitrate aqueous solution (40 mM, 2 mL). The synthetic route of HA-PDA is shown in Scheme 2;

[0088]

[0089] Route 2

[0090] After mixing for 30 minutes, the reaction solution was taken out, centrifuged and washed with water three times, and finally dispersed in 300 μL of water;

[0091] The cross-linking agent 8-arm-PEG-SH was fluorescently labeled, and then the above dispersion was mixed with a sodium acetate buffer solution (50 mM, pH 5.5) containing 8-arm-PEG-SH (10 kDa, 5 mg / mL), and then transferred to a dialysis bag with a molecular weight cutoff of 3.5 kDa. The dialysis bag was placed in a sodium acetate buffer solution (50 mM, pH 5.5) and the timing was started. 100 μL of the reaction solution was taken out from the dialysis bag at 10 minutes, 20 minutes, 30 minutes and 70 minutes of dialysis, centrifuged and washed twice with water, and then redispersed in 100 μL of water and fluorescence imaging was performed using a confocal microscope. The results are shown in FIG. Figure 7 The experimental data showed that the crosslinker 8-arm-PEG-SH first crosslinked with the polymer HA-PDA gradually exposed from the surface of ZIF-8, resulting in a hollow structure observed under a confocal microscope. With the further degradation of ZIF-8, the crosslinking of 8-arm-PEG-TNB and HA-PDA was also completed from the outside to the inside, and finally solid HA polymer nanoparticles were obtained.

[0092] Example 7

[0093] The preparation of OVA nanoparticles and their application in antigen delivery are as follows:

[0094] 8-arm-PEG-OH (40 kDa, 10 mg) and OVA (2 mg) were dissolved in 2-methylimidazole aqueous solution (160 mM, 2 mL), then added to zinc nitrate aqueous solution (40 mM, 2 mL) and mixed for 30 minutes to prepare OVA@ZIF-8 nanoparticles. Subsequently, 8-arm-PEG-NDEC was used as a cross-linking agent in sodium acetate buffer solution (50 mM, pH 5.5) to complete the cross-linking reaction and prepare OVA nanoparticles. OVA is a model antigen protein commonly used in immunotherapy, and the OVA nanoparticles can be degraded under reducing conditions to release free OVA, which can be used for antigen delivery.

[0095] Performance Test:

[0096] (1) OVA responsive release experiment

[0097] After adding fluorescently labeled OVA nanoparticles to GSH (10 mM) solution, the reaction solution was taken out at 1 hour, 2 hours, 3 hours, 5 hours, 8 hours, 12 hours, 24 hours and 48 hours, and the concentration of OVA in the supernatant was tested using Nanodrop after centrifugation. The release curve of OVA was plotted as follows: Figure 8The experimental results show that under reducing conditions, OVA nanoparticles will gradually degrade, thereby achieving responsive and sustained release of OVA.

[0098] (2) Cell uptake experiment

[0099] 100,000 RAW 264.7 cells were plated in each well of a 24-well plate and cultured overnight to allow the cells to adhere. After incubating the 264.7 cells with fluorescently labeled free OVA and OVA nanoparticles for 6 hours, the cells were collected and tested using a flow cytometer. The test results are shown in Figure 2. Fig. 9 As shown in the figure, OVA nanoparticles can increase the uptake of OVA in RAW 264.7 cells compared with free OVA, which indicates that OVA nanoparticles can promote the cellular uptake of OVA.

[0100] (3) Maturation experiment of bone marrow-derived DC cells (BMDC)

[0101] After PBS, free OVA and OVA nanoparticles were co-incubated with BMDC cells for 24 h, BMDC cells were collected and stained with anti-CD11c and anti-OVA257-264 (SIINFEKL)-H-2Kb, and then the expression of CD80 and CD86 was detected by flow cytometry. Fig.10 As shown, compared with free OVA, the OVA nanoparticles prepared by this method can promote the maturation of BMDCs.

[0102] (3) Antigen presentation experiment

[0103] After PBS, free OVA and OVA nanoparticles were co-incubated with BMDC cells for 24 h, BMDC cells were collected and stained with anti-CD11c, anti-CD80 and anti-CD86, and then the expression of SIINFEKL was detected by flow cytometry. Fig.11 As shown, compared with free OVA, the OVA nanoparticles prepared by this method can significantly promote antigen presentation in BMDCs.

[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A universal method for preparing polymer nanoparticles, characterized in that: The mineralizer and the polymer precursor are dissolved in a 2-methylimidazole aqueous solution, and then the solution is mixed with a zinc nitrate aqueous solution. After the reaction, the supernatant is removed by centrifugation, and then the product is redispersed in water and washed by centrifugation to obtain ZIF-8 nanoparticles encapsulating the polymer; then the ZIF-8 nanoparticles are dispersed in an acidic buffer solution containing a polymer cross-linking agent, the reaction solution is poured into a dialysis bag and placed in the acidic buffer solution to perform degradation of ZIF-8 and cross-linking reaction between the polymer precursor and the polymer cross-linking agent, and after the reaction is completed, the reaction solution in the dialysis bag is taken out and centrifuged, and the product is washed with water to obtain polymer nanoparticles; The mineralizer is PEG; the polymer precursor is various polymers; when the prepared polymer nanoparticles are PEG nanoparticles, PEG is both a mineralizer and a polymer precursor; The PEG is 8-arm-PEG-Maleimide (8-arm-PEG-MAL), 8-arm-PEG-4-nitrophenyl-2-(2-pyridyldithio)ethyl carbonate (8-arm-PEG-NDEC) or 8-arm-PEG-NH2, and its molecular weight is 10 kDa, 20 kDa or 40 kDa; The polymer cross-linking agents were 8-arm-PEG-2-nitro-5-thiobenzoate (8-arm-PEG-TNB), 8-arm-PEG-SH, 8-arm-PEG-NH2, or 8-arm-PEG-CHO, with molecular weights of 10 kDa, 20 kDa, and 40 kDa; The cross-linking reactions that occurred were thiol-disulfide exchange reaction, click chemistry reaction, amidation reaction and Schiff base reaction.

2. The universal method for preparing polymer nanoparticles according to claim 1, characterized in that: The molecular weight of 8-arm-PEG-MAL is 20 kDa, the molecular weight of 8-arm-PEG-NDEC is 40 kDa, and the molecular weight of 8-arm-PEG-NH2 is 20 kDa.

3. The universal method for preparing polymer nanoparticles according to claim 1, characterized in that: The molecular weight of the polymer cross-linking agent is 8-arm-PEG-TNB with a molecular weight of 10 kDa, 8-arm-PEG-SH with a molecular weight of 20 kDa, 8-arm-PEG- NH2 with a molecular weight of 10 kDa, and 8-arm-PEG-CHO with a molecular weight of 10 kDa.

4. The universal method for preparing polymer nanoparticles according to claim 1, characterized in that: The concentration of PEG in the 2-methylimidazole aqueous solution is 2.5-100 mg mL -1 ; The concentration of polymer cross-linking agent is 0.2-15 mg mL -1 ; The concentration of 2-methylimidazole in the 2-methylimidazole aqueous solution is 120-200 mM; the concentration of zinc nitrate in the zinc nitrate aqueous solution is 30-70 mM; the volume ratio of the 2-methylimidazole aqueous solution to the zinc nitrate aqueous solution is (1-2): (1-2).

5. The universal method for preparing polymer nanoparticles according to claim 1, characterized in that: The volume ratio of the 2-methylimidazole aqueous solution to the zinc nitrate aqueous solution is 1:1; the centrifugal speed used for centrifuging the ZIF-8 nanoparticles is 1000-10000 rcf.

6. The universal method for preparing polymer nanoparticles according to claim 1, characterized in that: The reaction time for preparing ZIF-8 nanoparticles encapsulating polymer precursors is 20-40 minutes.

7. The universal method for preparing polymer nanoparticles according to claim 1, characterized in that: The time for the degradation of ZIF-8 and the cross-linking reaction of PEG molecules is 1-8 hours.

8. The universal method for preparing polymer nanoparticles according to claim 1, characterized in that: The acidic buffer solution is a sodium acetate buffer solution with a concentration of 50 mM and a pH of 5.5-6.0; when dialysis is performed in the acidic buffer solution, a dialysis bag with a molecular weight cutoff of 1-7 kDa is used.

9. The universal method for preparing polymer nanoparticles according to claim 1, characterized in that: The molecular weight cut-off of the dialysis bag was 3.5 kDa.

10. The polymer nanoparticles prepared by the universal method for preparing polymer nanoparticles according to any one of claims 1 to 9.

11. A universal method for preparing nanoparticles suitable for various polymers, characterized in that: The steps include: The mineralizer and the polymer precursor are dissolved together in a 2-methylimidazole aqueous solution, and then the solution is mixed with a zinc nitrate aqueous solution, reacted for 30 minutes, centrifuged to remove the supernatant, and then the product is redispersed in water and washed by centrifugation to obtain ZIF-8 nanoparticles encapsulating the polymer precursor; then the ZIF-8 nanoparticles are dispersed in an acidic buffer solution containing a polymer crosslinking agent, the reaction solution is poured into a dialysis bag, and then placed in the acidic buffer solution to perform degradation of ZIF-8 and crosslinking reaction between the polymer precursor and the polymer crosslinking agent, the reaction solution in the dialysis bag is taken out and centrifuged, and the product is washed with water to obtain polymer nanoparticles; The mineralizer is 8-arm-PEG-OH; the polymer cross-linking agent is 8-arm-PEG-TNB; The polymer precursor includes thiolated hyaluronic acid (HA-SH), thiolated polylysine (PLL-SH), thiolated ovalbumin (OVA-SH) or lysozyme (LYZ).

12. The universal method for preparing nanoparticles applicable to various polymers according to claim 11, characterized in that: The concentration of 8-arm-PEG-OH in 2-methylimidazole aqueous solution is 2.5-100 mg mL -1 The concentration of 8-arm-PEG-TNB in ​​the acidic buffer solution was 0.2-15 mg mL -1 The cross-linking reaction that occurs is a thiol-disulfide bond exchange reaction.

13. The universal method for preparing nanoparticles applicable to various polymers according to claim 11, characterized in that: The concentration of 8-arm-PEG-OH in 2-methylimidazole aqueous solution was 5 mg mL -1 .

14. Polymer nanoparticles prepared according to the universal method for preparing nanoparticles from various polymers according to any one of claims 11 to 13.

15. Use of the polymer nanoparticles according to claim 14 in preparing products in the biomedical field.

Citation Information

Patent Citations

  • Protein (at) ZIF-8N nano material as well as preparation and application thereof

    CN112957343A